2013
DOI: 10.1007/s11103-013-0058-8
|View full text |Cite
|
Sign up to set email alerts
|

Excision of a selectable marker gene in transgenic banana using a Cre/lox system controlled by an embryo specific promoter

Abstract: Antibiotic and herbicide resistance genes have been used in transgene technology as powerful selection tools. Nonetheless, once transgenic events have been obtained their presence is no longer needed and can even be undesirable. In this work, we have developed a system to excise the selectable marker and the cre recombinase genes from transgenic banana cv. 'Grande Naine' (Musa AAA). To achieve this, the embryo specific REG-2 promoter was isolated from rice and its expression pattern in banana cell clumps, soma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Recently, Chong-Perez et al (2013) reported that the feasibility of using developmentally controlled promoters to mediate marker excision in banana. Considering that the LEAFY gene is the key gene affecting plant flowering development, in order to complete the removal of exogenous genes in early fruit formation, in this study the LFY promoter of the flower-determination gene LEAFY from A. thaliana genome was cloned (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Chong-Perez et al (2013) reported that the feasibility of using developmentally controlled promoters to mediate marker excision in banana. Considering that the LEAFY gene is the key gene affecting plant flowering development, in order to complete the removal of exogenous genes in early fruit formation, in this study the LFY promoter of the flower-determination gene LEAFY from A. thaliana genome was cloned (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This technology utilizes a combination of two site-specific recombinant enzyme components, i.e. the Cre/LoxP system derived from bacterial phages (Chong-Perez et al 2013;Odell et al 1990;Zhang et al 2003) and FLP/FRT from yeast (Woo et al 2009). The two sets of site-specific synthetic recombinase components are comprehensively utilized to drive the recombinase FLP or Cre to express at a suitable time and site, using a specific promoter (Luo et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To delete the marker genes, site-specific recombination systems have been widely applied to Arabidopsis, tobacco, and other crops, and woody plants, often using Cre/ loxP or Flp/ FRT methods. Cre/ loxP was successfully used in Arabidopsis, tobacco, rice, bananas, citrus, and maize [ 29 , 30 , 31 , 32 , 33 , 34 ]. Flp/ FRT has been used in grapevine and apples, with non-efficient excision efficiency [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The marker-excision process is initiated in the resulting F1 hybrids, and stable marker-free lines are identified among F2 progeny that segregate the marker-free locus from the cre gene. Other approaches, involving inducible cre gene or tissue-specific cre expression, have also been successful in isolating 'stable' marker-free plant lines (Chong-Pérez et al 2013;Khattri et al 2011;Sreekala et al 2005). FLP-FRT is analogous to Cre-lox consisting of FLP recombinase and a 34-bp FLP-recombination target (FRT).…”
Section: Introductionmentioning
confidence: 99%